Esqualeno: explorando fontes alternativas para seu emprego nas indústrias farmacêutica e cosmética - Neves, Aquila de Souza (Brasil, 2024)
Squalene, a natural compound with essential roles in the biosynthesis of cholesterol and applications in the cosmetics and pharmaceutical industries, faces challenges in sustainable production, especially when extracted from animal sources such as deep-sea sharks. This research focuses on the search for sustainable alternatives, with an emphasis on the production of squalene by microorganisms. The methodology employed involved an exploratory literature review, consulting indexed databases, with inclusion and exclusion criteria. The industry's growing demand for squalene, whether for cosmetics or vaccine adjuvants, is driving the exploration of sustainable sources. Biotechnology plays a key role, offering promising production methods. Research has explored various strategies, including the use of microorganisms, mainly yeasts, some fungi and microalgae for squalene production. Although these approaches show potential, there are challenges regarding costs, optimization and complexity. The use of Brazilian sugar cane by Amyris stands out as a sustainable solution. Finally, there is a great need for research into alternative sources of squalene to meet the growing demand from industry, considering the environmental impact caused by predatory shark hunting.